2021
DOI: 10.1111/ajo.13437
|View full text |Cite
|
Sign up to set email alerts
|

Training in obstetric anal sphincter injuries in Australia and New Zealand: A survey of Royal Australian and New Zealand College of Obstetricians and Gynaecologists trainees

Abstract: Background:Training in obstetric anal sphincter injuries (OASIS) in Australia and New Zealand relies upon consultant teaching and has not previously been assessed. Aims:The aims of this study are to establish if training in OASIS is consistent and optimal in Australia and New Zealand and to evaluate trainee perspectives on supervision and teaching, along with confidence in repairing OASIS. Materials and Methods: A descriptive cross-sectional study was performed. Royal Australian and New Zealand College of Obst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The percentage of physicians who had attended training courses in Australia and New Zealand was similar (75.8%) [ 19 ], whereas in the American survey, only 44% had had formal training in obstetric trauma classification and diagnosis [ 20 ]. This shows a huge improvement in training in obstetric tears in the last 20 years in the UK.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The percentage of physicians who had attended training courses in Australia and New Zealand was similar (75.8%) [ 19 ], whereas in the American survey, only 44% had had formal training in obstetric trauma classification and diagnosis [ 20 ]. This shows a huge improvement in training in obstetric tears in the last 20 years in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that some technical skills decline in performance over time after the course [ 27 ]. When asked for suggestions for improving training in OASIs, 38.6% of Australian and New Zealand physicians asked for mandatory workshops, with some suggesting that these should be yearly [ 19 ]. We propose that attending a refresher course, every 3 to 5 years, could improve knowledge and confidence in the management of perineal trauma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations